Natural frequency analysis of cracked beam - Khiem, Nguyen Tien; Mai, Dao Nhu (Vietnam Journal of Mechanics, 1997)
The model of cracked one-dimensional structure has been treated as two uniform beams connected by an equivalent rotation spring at the crack location. The frequency equation in bending vibration of the system is obtained in general form for arbitrary boundary conditions at both ends used for analysing the natural frequencies as function of crack position and magnitude. This investigation allows to carry out general procedure for identification of position as well as magnitude of the crack by natural frequencies measured experimentally.